2019
DOI: 10.35371/aoem.2019.31.e19
|View full text |Cite
|
Sign up to set email alerts
|

Night shiftwork and prostate-specific antigen level in a tire manufacturing factory

Abstract: BackgroundRecent studies suggest that night shiftwork may increase the risk of prostate cancer and elevated serum prostate-specific antigen (PSA) level. The purpose of this study was to verify whether rotating night shiftwork affects serum PSA level.MethodsThis study included 3,195 male production workers who work in a large tire manufacturing factory. Serum PSA levels were measured and the data on related factors were obtained.ResultsThe mean serum PSA level was 0.98 ± 0.79 ng/mL. PSA levels were significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In the metabolic system subcategory (n = 13), there was an emphasis on the problems of the system itself [94][95][96][97][98][99][100], obesity [60,104], and diabetes [85,[101][102][103]. The association between breast cancer [105][106][107][108][109][110] or prostate cancer [111,112] and work schedules was studied several times, representing a total of 10 references to oncological problems. Both the immune system [50,[115][116][117][118][119], as well as well-being and quality of life [69,71,[120][121][122][123], had six references each.…”
Section: Resultsmentioning
confidence: 99%
“…In the metabolic system subcategory (n = 13), there was an emphasis on the problems of the system itself [94][95][96][97][98][99][100], obesity [60,104], and diabetes [85,[101][102][103]. The association between breast cancer [105][106][107][108][109][110] or prostate cancer [111,112] and work schedules was studied several times, representing a total of 10 references to oncological problems. Both the immune system [50,[115][116][117][118][119], as well as well-being and quality of life [69,71,[120][121][122][123], had six references each.…”
Section: Resultsmentioning
confidence: 99%
“…A study of the National Health and Nutrition Examination Survey reported an association with shift work and elevated PSA levels, which implicates that shift workers had a higher risk of developing prostate cancer [ 21 ]. On the other hand, another study of Korean workers in tire manufacturing indicated that night shift work did not show increased PSA levels [ 22 ]. Although there have been many studies on the relationship between shift work and prostate cancer, there is still the need for further research because of the inconsistency of the relationship [ 12 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%